Does human resource information system influence performance management? - Muddapu Raja; T. N. V. R. L. Swamy; Saumendra Das; Rohit Bansal; Mochammad Fahlevi; Aulia Luqman Aziz (Cogent Business & Management)
Human resource information system (HRIS) integrates information technology into human resource management to enhance efficiency. Thus, to understand its importance in performance management, the present study aims to determine the influence of HRIS on performance management (PM) and identify the current research gaps. For these purposes, it followed five stages of systematic literature review and identified 221 documents from Scopus and the Web of Science from 2001 to 2024. After filtering, 41 articles were processed for further review and analysis. The results of the current study identified 95 influencing factors of HRIS for different purposes and contexts, and 69 variables needed further validation. This opens a massive opportunity for future researchers to test these relations. The analysis also revealed a considerable gap between empirical and review articles, suggesting that more review-based studies should be conducted. Meanwhile, the current study shows that India dominates other nations regarding target population selection. Furthermore, the study theoretically found that a human resource information system influences performance management. However, practical evidence was unavailable; therefore, future researchers could empirically test this relationship. Additionally, it provides several future directions for researchers to focus on contributing more to HRIS and performance management.